2008
DOI: 10.4103/1817-1737.37948
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous computed tomography-guided core biopsy for the diagnosis of mediastinal masses

Abstract: AIM:To describe various approaches of computed tomography (CT)-guided core biopsy and evaluate its ability to obtain adequate tissue for the assessment of mediastinal masses.MATERIALS AND METHODS:Between February 2004 and October 2006, 83 percutaneous CT-guided biopsies of mediastinal lesions were performed on 82 patients under local anesthesia. Coaxial needles were used and minimum of 3-4 cores were obtained. Post-biopsy CT scan was performed and patients observed for any complications. Tissue samples were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…Reported accuracy rates of CT guided percutaneous needle aspiration/biopsy ranges from 64%-97% with a small risk of complications, and these results were observed by B Morrissey et al [1], Westcott JL et al [3]. Our study produced a better diagnostic yield as compared to other similar study conducted by Kulkarni et al who had reported a diagnostic yield of 96% [5].…”
Section: Discussioncontrasting
confidence: 53%
“…Reported accuracy rates of CT guided percutaneous needle aspiration/biopsy ranges from 64%-97% with a small risk of complications, and these results were observed by B Morrissey et al [1], Westcott JL et al [3]. Our study produced a better diagnostic yield as compared to other similar study conducted by Kulkarni et al who had reported a diagnostic yield of 96% [5].…”
Section: Discussioncontrasting
confidence: 53%
“…[1314] Diagnostic yield was low (74.2%) for mediastinal procedures in our series where as in previous series, it is 83.6–96%. [1516]…”
Section: Discussionmentioning
confidence: 99%
“…[17] Fusion positron emission tomography-CT images of many patients were available in the series by Kulkarni et al ., which help in targeting the metabolically active portion of the lesion. [15] In many series, the biopsies were done by an experienced and dedicated operators while in our setup, some of the cases were done by a less experienced resident. Apart from these, the most important reason for the high diagnostic yield in other series was the availability of follow-up and a nonspecific benign pathology result was considered diagnostic if the lesion had a benign course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique under guidance of fluoroscopy, ultrasonography, or computed tomography (CT) allows sufficient tissue sampling for accurate histologic and immunohistochemical evaluation; thereby it could highlight the need for further mediastinoscopy, mediastinotomy, thoracoscopy, or open chest surgery. [ 1 2 3 4 ] Previous reports have been shown higher accuracy of histology in comparison with cytology in evaluation of mediastinal lesions. [ 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%